Blooming through the Cracks: The Case of Syrian Women in Egypt After 2011 - Dayeh, Ola (AUC Knowledge Fountain, 2024)
This study was conducted in 2023 and aims to understand the impact of displacement on Syrian women’s involvement in the public sphere in Egypt. After the transition of the Syrian revolution into an armed conflict, Syrians witnessed a large wave of displacement, looking for safety away from their homeland. The research defines displacement as the movement of people who are forced to leave their place of residence. The focus is directed on the situation of Syrian women who were displaced to Egypt after 2011, and it proves the claims that there is an increase in women’s engagement in the public sphere because of displacement. Moreover, this thesis aims to compare the level of civic engagement upon displacement to that happening prior to displacement. The fieldwork has been done with Syrian women and men in different locations in Cairo and Giza. It integrates their perceptions of women’s role in the community during displacement within the research findings. This study was encouraged by the lack of studies highlighting women’s and men’s perceptions regarding women’s experience in the public sphere in Egypt, especially after their displacement reached its twelfth year.